Road paving composition
The road paving composition, which integrates a polyamide emulsion with an epoxysilane-based coupling agent, addresses the issue of insufficient abrasion resistance in existing technologies, resulting in a wear-resistant and flexible paving solution with a good pot life.
Patent Information
- Application Number
- JP2021093185
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-02
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2041-06-02
AI Technical Summary
Existing road paving compositions face challenges with insufficient abrasion resistance and limited improvement in wear resistance when using polyamide resins and hardeners.
A road paving composition combining a polyamide emulsion with an epoxysilane-based coupling agent, optionally including silica sand and a pigment for color paving, to enhance wear resistance and flexibility.
The composition achieves improved abrasion resistance and maintains a good pot life, even when using a hardener, thereby providing a durable and effective road paving solution.
Smart Images

Figure 0007657101000001 
Figure 0007657101000002 
Figure 0007657101000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a road paving composition and a colored paving coating composition. [Background technology]
[0002] In recent years, due to the diversification of traffic conditions, sidewalks and bicycle paths that are clearly distinguished from roadways have been increasingly constructed. By using colored pavement for such pavement, the roadway can be clearly distinguished from the bicycle path or sidewalk by coloring. Colored pavement is mainly made using water dispersions of acrylic resin or polyester resin. Patent Document 1 discloses a road paving composition that can be applied at room temperature, develops sufficient strength soon after application, and enables efficient formation or repair of pavements. The road paving composition contains an aqueous dispersion in which a resin (A) having a specific acid value is neutralized with a basic compound, and a silane coupling agent having an alkoxy group having 1 to 5 carbon atoms and an amino group, and serves as a binder for aggregates in road paving or a surface layer of a pavement. The road paving composition can be applied at room temperature, develops sufficient strength soon after application, and enables efficient formation or repair of a pavement. Polyamide resins are also known as resins that are expected to bond strongly to aggregates and improve the water resistance of coating films. Patent Document 2 discloses an aqueous dispersion that is substantially free of emulsifiers or surfactants and can provide a polyamide resin coating film having good adhesion, flexibility, chemical resistance, and heat-resistant adhesion, and that has excellent dispersion stability even at room temperature and a small particle size sufficient to form a dense coating film, the aqueous dispersion containing a specific amount of dimer acid as a dicarboxylic acid component and a dimer acid-based polyamide resin having a specific acid value and a specific number average particle size dispersed in an aqueous medium, the aqueous dispersion containing a specific basic compound and substantially free of a specific aqueous dispersing aid. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2005-126998 A [Patent Document 2] JP 2011-094072 A Summary of the Invention [Problem to be solved by the invention]
[0004] In the technique described in Patent Document 1, the abrasion resistance of the pavement may be insufficient. In addition, when using the polyamide resin described in Patent Document 2, it is expected that the amide bond will firmly bond with the aggregate and improve the abrasion resistance, but there are cases in which further improvement in abrasion resistance cannot be seen by adding a hardener. The present invention relates to a road paving composition having abrasion resistance. [Means for solving the problem]
[0005] The present invention relates to the following [1] to [4]. [1] A road paving composition comprising a polyamide emulsion (A) and an epoxy silane coupling agent (B). [2] The road paving composition according to [1] above, further comprising silica sand. [3] A colored pavement coating composition, comprising the road pavement composition according to [2] above, further comprising a pigment. [4] A method for paving a road, comprising the steps of mixing a polyamide emulsion (A) with an epoxy silane coupling agent (B) and applying the resulting mixture to a pavement surface. Effect of the Invention
[0006] According to the present invention, a road paving composition having abrasion resistance can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] [Road paving composition] The road paving composition of the present invention contains a polyamide emulsion (A) and an epoxy silane coupling agent (B). According to the above, a road paving composition having abrasion resistance can be obtained. Furthermore, this technology can be applied to provide a colored paving coating composition. Although the detailed mechanism by which the effects of the present invention are obtained is unclear, it is believed that part of it is as follows. For example, when an amine-based silane coupling agent is used, the carboxylic acid of the polyamide and the amine of the silane coupling agent cannot form an ionic bond, and the curing reaction via the polyamide does not occur, so it is speculated that no improvement in abrasion resistance was observed. In the present invention, by using an epoxy-based silane coupling agent, the epoxy group and the carboxylic acid terminal are covalently bonded by the epoxy ring-opening reaction, and the curing reaction via the polyamide proceeds. Therefore, it was found that the abrasion resistance is also improved.
[0008] [Polyamide emulsion (A)] The polyamide emulsion (A) is an O / W type emulsion in which the polyamide (a1) is dispersed in an aqueous medium. The aqueous medium is a dispersion medium in which water accounts for the largest proportion by mass. From the viewpoint of abrasion resistance, the water content in the aqueous medium is preferably 60 mass% or more, more preferably 75 mass% or more, and even more preferably 90 mass% or more, and 100 mass% or less. Examples of components other than water include water-soluble organic solvents such as alkyl alcohols having 1 to 5 carbon atoms, such as methanol and ethanol; dialkyl ketones having 3 to 5 carbon atoms, such as acetone and methyl ethyl ketone; and cyclic ethers, such as tetrahydrofuran. In one preferred embodiment of the present invention, the aqueous medium consists essentially of water.
[0009] The solid content in the polyamide emulsion is preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 20% by mass or more from the viewpoint of abrasion resistance, and is preferably 50% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less from the viewpoint of dispersibility.
[0010] The volume median particle size (D 50 From the viewpoint of dispersibility, the average particle diameter is preferably 50 nm or more, more preferably 80 nm or more, and even more preferably 100 nm or more, and is preferably 1500 nm or less, more preferably 1000 nm or less, and even more preferably 300 nm or less. The volume median particle size can be appropriately adjusted by adjusting the molecular weight, acid value, and degree of neutralization of the polyamide (a1) and by changing the phase inversion emulsification conditions. In this specification, the volume median particle size (D 50 The volume median particle size (D) is the particle size at which the cumulative volume frequency calculated by volume fraction is 50% from the smallest particle size. 50 ) can be determined by the method described in the Examples below.
[0011] <Polyamide (a1)> Polyamide is a polymeric compound having an amide bond (-CONH-) and includes a component derived from a carboxylic acid component and a component derived from an amine component. In other words, it is a polycondensation product of a carboxylic acid component and an amine component. Polyamide can be obtained by a condensation polymerization reaction between a carboxylic acid component and an amine component, a ring-opening polymerization reaction of a cyclic lactam, a self-condensation reaction of an amino acid or its derivative, or the like.
[0012] (Carboxylic acid component) As the carboxylic acid component, a monobasic carboxylic acid, a dibasic carboxylic acid, or a polymerized fatty acid can be used. The monobasic carboxylic acid includes saturated or unsaturated aliphatic monobasic carboxylic acids having 4 or more carbon atoms, preferably 8 or more carbon atoms, more preferably 12 or more carbon atoms, and 24 or less carbon atoms, preferably 22 or less carbon atoms. Specific examples of the saturated aliphatic monocarboxylic acid include butyric acid, valeric acid, lauric acid, palmitic acid, stearic acid, arachidic acid, and behenic acid. Examples of unsaturated aliphatic monocarboxylic acids include oleic acid, linoleic acid, linolenic acid, eicosenoic acid, erucic acid, and mixed fatty acids obtained from natural fats and oils (tall oil fatty acids, rice bran fatty acids, soybean oil fatty acids, beef tallow fatty acids, etc.). The dicarboxylic acid may be an aliphatic or aromatic dicarboxylic acid having 4 or more carbon atoms, preferably 6 or more carbon atoms. Specific examples thereof include succinic acid, alkenylsuccinic acid, adipic acid, sebacic acid, dodecanedioic acid, phthalic acid, isophthalic acid, and terephthalic acid.
[0013] The polymerized fatty acid is a polymer obtained by polymerizing a monobasic fatty acid having an unsaturated bond, or a polymer obtained by polymerizing an ester of a monobasic fatty acid having an unsaturated bond. Examples of the polymerized fatty acid include those obtained by a dehydration condensation reaction of a divalent carboxylic acid derived from vegetable oils and fats. Examples of monobasic fatty acids having unsaturated bonds include unsaturated fatty acids having a total of 8 to 24 carbon atoms and typically having 1 to 3 unsaturated bonds, and specific examples thereof include oleic acid, linoleic acid, linolenic acid, natural drying oil fatty acids, and natural semi-drying oil fatty acids. Furthermore, examples of the esterification products of monobasic fatty acids having unsaturated bonds include esterification products of the above monobasic fatty acids having unsaturated bonds with aliphatic alcohols, preferably aliphatic alcohols having 1 to 3 carbon atoms. The polymerized fatty acid, which is a polymer obtained by polymerizing a monobasic fatty acid having an unsaturated bond or an ester of a monobasic fatty acid having an unsaturated bond, is preferably a polymer containing a dimer as a main component. For example, a polymer of an unsaturated fatty acid having 18 or more carbon atoms is commercially available that has a composition of 0 to 10 mass% of a monobasic acid (monomer) having 18 carbon atoms, 60 to 99 mass% of a dibasic acid (dimer) having 36 carbon atoms, and 30 mass% or less of a tribasic acid or more having 54 carbon atoms (trimer or more). The above carboxylic acid components can be used alone or in combination of two or more kinds, and it is more preferable to use a monobasic carboxylic acid and a polymerized fatty acid in combination.
[0014] The carboxylic acid component preferably contains at least a monovalent carboxylic acid, and the content thereof is preferably 5 molar equivalent % or more, more preferably 8 molar equivalent % or more, even more preferably 10 molar equivalent % or more, and preferably 50 molar equivalent % or less, based on the total amount of the carboxylic acid components, from the viewpoint of wear resistance. When a monobasic carboxylic acid and a polymerized fatty acid are used in combination as the carboxylic acid component, the content of the monobasic carboxylic acid is preferably 10 molar equivalent% or more, more preferably 15 molar equivalent% or more, and preferably less than 50 molar equivalent%, more preferably less than 40 molar equivalent%, based on the total amount of the carboxylic acid component. Also, the content of the polymerized fatty acid is preferably 50 molar equivalent% or more, more preferably 60 molar equivalent% or more, and preferably less than 90 molar equivalent%, more preferably less than 85 molar equivalent%, based on the total amount of the carboxylic acid component.
[0015] (amine component) Examples of the amine component include polyamines, aminocarboxylic acids, and aminoalcohols.
[0016] Examples of the polyamine include aliphatic diamines, aliphatic triamines, alicyclic diamines, and aromatic diamines. The aliphatic diamine is preferably an aliphatic diamine having 2 to 6 carbon atoms, and examples of such diamine include ethylenediamine, propylenediamine, butylenediamine, hexamethylenediamine, etc. Among these, ethylenediamine and hexamethylenediamine are preferred. Examples of the aliphatic triamine include diethylenetriamine, dipropylenetriamine, benzenetriamine, etc. Among these, diethylenetriamine is preferable. Examples of the alicyclic diamine include isophorone diamine, tricyclodecane diamine, and norbornane diamine. Among these, isophorone diamine is preferable. Examples of aromatic diamines include xylylenediamine, diphenylmethanediamine, diaminodiphenylsulfone, methylenebischloroaniline, etc. Among these, xylylenediamine is preferred.
[0017] From the viewpoint of wear resistance, the polyamine contains at least two or more polyamines of the same or different kinds selected from aliphatic diamines, aliphatic triamines, alicyclic diamines and aromatic diamines, at least one of which is an aliphatic diamine. Among them, the amine component contains, as the two or more polyamines, preferably one aliphatic diamine and one or more other aliphatic diamines, one or more aliphatic triamines, one or more alicyclic triamines and one or more aromatic diamines, totaling two or more polyamines, more preferably two or more aliphatic diamines and one or more alicyclic diamines, totaling three or more polyamines. By containing two or more polyamines with different structures in the amine component, the orientation of the amide groups between polyamide molecules can be adjusted. This can reduce the amount of crystallization and hydrogen bonds caused by intermolecular interactions of polyamide, and is therefore considered to be able to suppress the aggregation of the dispersion. Furthermore, by containing two or more polyamines with different structures, it is possible to lower the softening point of the polyamide, and the desired softening point can be easily adjusted. Note that, when the amine component is made of a single type, the polyamide tends to have a high softening point.
[0018] As the two or more aliphatic diamines, ethylenediamine and hexamethylenediamine are preferable, and as the alicyclic diamine, isophoronediamine is preferable.
[0019] In the polyamine, the polyamine species having the largest amount is preferably an aliphatic diamine, more preferably ethylenediamine. From the viewpoint of wear resistance, the amount of the polyamine species having the largest amount is preferably 55 mol% or more, more preferably 60 mol% or more, even more preferably 65 mol% or more, and preferably 85 mol% or less, more preferably 80 mol% or less, even more preferably 75 mol% or less, based on the total amount of the amine components. When an alicyclic diamine is contained, the content thereof is preferably 1 mol % or more, more preferably 2 mol % or more, even more preferably 3 mol % or more, and preferably 10 mol % or less, more preferably 8 mol % or less, even more preferably 7 mol % or less, based on the total amount of amines.
[0020] (Physical properties of polyamide) From the viewpoint of abrasion resistance, the softening point of the polyamide used in the present invention is preferably 60°C or higher, more preferably 70°C or higher, even more preferably 75°C or higher, even more preferably 80°C or higher, and is preferably 105°C or lower, more preferably 100°C or lower, even more preferably 95°C or lower. From the viewpoints of abrasion resistance and pot life, the acid value of the polyamide is preferably 15 mgKOH / g or more, more preferably 18 mgKOH / g or more, and even more preferably 22 mgKOH / g or more, and from the viewpoint of abrasion resistance, it is preferably 50 mgKOH / g or less, more preferably 40 mgKOH / g or less, and even more preferably 30 mgKOH / g or less. From the viewpoint of abrasion resistance, the amine value of the polyamide is preferably 0.1 mgKOH / g or more, more preferably 0.2 mgKOH / g or more, even more preferably 0.4 mgKOH / g or more, and preferably 7 mgKOH / g or less, more preferably 5 mgKOH / g or less, even more preferably 3 mgKOH / g or less. The softening point, acid value and amine value of the polyamide can be measured by the method described in the Examples. From the viewpoint of abrasion resistance, the polyamide preferably has a heat of crystallization (ΔHc) of 2 J / g or more, more preferably more than 2 J / g, even more preferably 3 J / g or more, and even more preferably 4.5 J / g or more, when cooled at 20° C. / min and 5° C. / min in differential scanning calorimetry (DSC) according to JIS-K7121, and from the viewpoint of abrasion resistance and pot life, the heat of crystallization (ΔHc) is preferably 13 J / g or less, more preferably 10 J / g or less, and even more preferably 8 J / g or less. The heat of crystallization (ΔHc) is the peak area of the crystallization peak temperature Tc (°C) that appears when the polyamide is heated at a heating rate of 20°C / min and cooled at a rate of 5°C / min. The measurement can be performed by the method described in the Examples.
[0021] (Degree of neutralization) From the viewpoint of dispersibility, the polyamide may be neutralized at least partially in acid groups. In this case, the amount of the neutralizing agent used is preferably 80 mol% or more, more preferably 90 mol% or more, even more preferably 95 mol% or more, and preferably 140 mol% or less, more preferably 120 mol% or less, even more preferably 110 mol% or less. Here, the degree of neutralization (mol %) can be specifically determined by the following formula: When the degree of neutralization is 100 mol % or less, it is synonymous with the use equivalent of the neutralizing agent. Degree of neutralization (mol%)=[{weight of neutralizing agent added (g) / equivalent weight of neutralizing agent} / [{acid value of polyamide (mgKOH / g) × weight of polyamide (g)} / (56 × 1,000)]] × 100 Examples of the neutralizing agent used for neutralizing the polyamide include basic compounds. Examples of the basic compounds include hydroxides of alkali metals or alkaline earth metals such as sodium hydroxide, potassium hydroxide, and calcium hydroxide, ammonia, and organic amines. From the viewpoint of high temperature stability, ammonia or organic amines are preferred. Examples of organic amines include triethylamine, N,N-diethylethanolamine, N,N-dimethylethanolamine, and triethanolamine. Nitrogen-containing basic substances are preferred, and N,N-dimethylethanolamine is more preferred.
[0022] (Production method of polyamide) The polyamide can be obtained by subjecting a carboxylic acid component and an amine component, preferably a carboxylic acid component containing a monovalent carboxylic acid and a polymerized fatty acid, and an amine component containing a polyamine, to a polycondensation reaction under known reaction conditions. From the viewpoint of wear resistance, the polyamide used in the present invention is preferably made to have an excess molar equivalent ratio of the carboxylic acid component to the amine component. Specifically, the molar equivalent ratio of the carboxyl group of the carboxylic acid component to the amino group of the amine component (carboxyl group / amino group) is preferably more than 1.0 / 1.0, more preferably 1.15 / 1.0 or more, even more preferably 1.1 / 1.0 or more, and is preferably 1.4 / 1.0 or less, more preferably 1.3 / 1.0 or less, even more preferably 1.25 / 1.0 or less. The polycondensation reaction temperature is preferably 180° C. or higher, more preferably 190° C. or higher, and preferably 250° C. or lower, more preferably 240° C. or lower. Polyamides can be easily produced by adjusting the reaction temperature and reaction time under the above molar equivalent ratio conditions of the carboxylic acid component and the amine component, and, in some cases, by adding a monovalent carboxylic acid or a monoamine.
[0023] [Carboxylic acid compound (a2)] From the viewpoints of abrasion resistance and pot life, the polyamide emulsion (A) preferably further contains a carboxylic acid compound. The carboxylic acid compound may be a monocarboxylic acid, a dicarboxylic acid, or a trivalent or higher polycarboxylic acid. From the viewpoints of wear resistance and pot life, a monocarboxylic acid is preferred. From the viewpoints of abrasion resistance and pot life, the carboxylic acid compound has a carbon number of 8 or more, preferably 10 or more, more preferably 12 or more, and even more preferably 14 or more, and has a carbon number of 24 or less, preferably 23 or less, more preferably 22 or less, and even more preferably 20 or less.
[0024] Among these, the carboxylic acid compound is preferably at least one carboxylic acid compound (a2) selected from branched chain aliphatic carboxylic acids having 8 to 24 carbon atoms and secondary carboxy group-containing linear aliphatic carboxylic acids having 8 to 24 carbon atoms. The term "secondary carboxy group" refers to a carboxy group in which the carbon atom to which the carboxy group is bonded is a secondary carbon atom having two carbon atoms bonded thereto. Specific examples of branched chain aliphatic carboxylic acid compounds having 8 to 24 carbon atoms and secondary carboxy group-containing linear aliphatic carboxylic acid compounds having 8 to 24 carbon atoms include isostearic acid (2,2,4,8,10,10-hexamethylundecane-5-carboxylic acid), 16-methylheptadecanoic acid, 2-hexyldecanoic acid, 2-ethylhexanoic acid, 4-methylnonanoic acid, octyldecanoic acid, hexyldodecanoic acid, isoarachic acid, 2-propylvaleric acid, etc. These carboxylic acid compounds may be used alone or in combination.
[0025] The content of the carboxylic acid compound (a2) in the polyamide emulsion (A) is, from the viewpoints of abrasion resistance and pot life, preferably 0 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 6 parts by mass or more, per 100 parts by mass of the total content of the polyamide (a1) and the carboxylic acid compound (a2); and from the viewpoint of abrasion resistance, it is preferably 20 parts by mass or less, more preferably 18 parts by mass or less, and even more preferably 14 parts by mass or less. In other words, the mass ratio of the polyamide (a1) to the carboxylic acid compound (a2) [(a1):(a2)] is, from the viewpoint of abrasion resistance, preferably 80:20 or more, more preferably 82:18 or more, even more preferably 86:14 or more, and is preferably 100:0 or less, more preferably 99:1 or less, even more preferably 97:3 or less, even more preferably 94:6 or less.
[0026] [Production method of polyamide emulsion] The polyamide emulsion can be produced by a known method for dispersing polyamide. For example, the polyamide (a1) and, if necessary, the carboxylic acid compound (a2) are forcedly emulsified in an aqueous medium, if necessary, in the presence of a surfactant, by an emulsifier, or a phase inversion emulsification method can be mentioned. From the viewpoint of abrasion resistance and pot life, the polyamide emulsion is preferably produced by a phase inversion emulsification method.
[0027] [Process 1] A preferred embodiment of the method for producing a polyamide emulsion includes the following step 1. Step 1: A step of adding an aqueous medium to an organic solvent solution of a polyamide (a1) and, if necessary, a carboxylic acid compound (a2) to effect phase inversion emulsification. (Organic solvent) The organic solvent solution in step 1 is a solution in which polyamide (a1) and, if necessary, carboxylic acid compound (a2) are dissolved in an organic solvent. Examples of the organic solvent include acetone, isopropyl alcohol, methyl ethyl ketone, and tetrahydrofuran (THF), and preferred are organic solvents that are water-soluble and have a boiling point lower than that of water. In particular, the organic solvent is preferably a mixed solvent of isopropyl alcohol and THF. In this case, the mass ratio of isopropyl alcohol / THF is preferably 40 / 60 or more, more preferably 45 / 55 or more, and preferably 60 / 40 or less, more preferably 55 / 45 or less, and even more preferably 50 / 50 or less. The amount of the organic solvent used is preferably 80 parts by mass or more, more preferably 90 parts by mass or more, and 200 parts by mass or less, more preferably 150 parts by mass or less, per 100 parts by mass of the total mass of the polyamide (a1) and, if necessary, the carboxylic acid compound (a2). From the viewpoint of abrasion resistance, the temperature of the organic solvent phase (oil phase) during phase inversion emulsification is preferably 10°C or higher, more preferably 15°C or higher, even more preferably 20°C or higher, and preferably 70°C or lower, more preferably 50°C or lower, even more preferably 40°C or lower.
[0028] (aqueous medium) In step 1, an aqueous medium is added to the organic solvent solution, preferably with stirring. As the aqueous medium, the aqueous medium described above can be used. The amount of the aqueous medium used is preferably 100 parts by mass or more, more preferably 200 parts by mass or more, and 1000 parts by mass or less, more preferably 600 parts by mass or less, per 100 parts by mass of the total mass of the polyamide (a1) and the carboxylic acid compound (a2) which may be included as necessary. In order to neutralize the polyamide (a1), a basic compound is preferably further added together with the aqueous medium. In addition, the volume median particle size (D 50 In order to adjust the viscosity, a surfactant may be further added. The amount of the surfactant used is preferably 20 parts by mass or less, more preferably 5 parts by mass or less, based on 100 parts by mass of the polyamide (A).
[0029] (Phase inversion emulsification) In the phase inversion emulsification, an aqueous medium and, if necessary, a basic compound and a surfactant are added, and then the organic solvent is preferably distilled off to invert the phase into an aqueous medium. The organic solvent is distilled off under reduced pressure conditions, preferably from 8 kPa to 50 kPa, and at a temperature of preferably from 25° C. to 70° C. It is preferable to distill off the organic solvent so that the content of the organic solvent in the emulsion for road paving is preferably 1% by mass or less, more preferably 0.1% by mass or less. It is also preferable to add a basic compound or the like to the resulting treatment liquid to adjust the pH to 6 or more and 10 or less.
[0030] In this manner, an emulsion for road paving, which is a water dispersion, is produced. The emulsion for road paving of the present invention may be the aqueous dispersion obtained as described above, or may further contain an aqueous medium.
[0031] [Epoxy silane coupling agent (B)] The road paving composition of the present invention contains an epoxy silane coupling agent (B) as a curing agent. Examples of the epoxy silane coupling agent (B) include epoxy silane coupling agents having an alkoxy group and a glycidyl group having 1 to 5 carbon atoms, such as 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, etc. These epoxy silane coupling agents can be used alone or in combination of two or more. Among these, from the viewpoints of abrasion resistance and pot life, preferred are epoxy silane coupling agents having a dialkoxysilyl group, such as 3-glycidoxypropylmethyldimethoxysilane and 3-glycidoxypropylmethyldiethoxysilane, and more preferred are epoxy silane coupling agents having a dimethoxysilyl group, such as 3-glycidoxypropylmethyldimethoxysilane. Commercially available epoxy silane coupling agents (B) include KBM-303, KBM-402, KBM-403, KBE-402, and KBE-403 manufactured by Shin-Etsu Chemical Co., Ltd.
[0032] From the viewpoint of abrasion resistance, the content of the epoxy silane coupling agent (B) is preferably 5 parts by mass or more, more preferably 6 parts by mass or more, and even more preferably 7 parts by mass or more, per 100 parts by mass of the solid content of the polyamide emulsion (A), and from the viewpoint of pot life, it is preferably 12 parts by mass or less, more preferably 11 parts by mass or less, and even more preferably 10 parts by mass or less.
[0033] 〔aggregate〕 The road paving composition may further contain aggregate. The aggregate roughens the surface and provides a slip effect. Furthermore, when the road pavement is a drainage pavement using an asphalt mixture, the hardened road pavement composition forms a layer to cover the aggregate in the voids of the drainage pavement, and the aggregate can be more firmly bonded. Examples of aggregates include natural aggregates such as gravel and sand; processed aggregates such as crushed stone, crushed sand, and fillers; recycled aggregates; and artificial materials such as ceramics and slag. Specific examples of crushed sand include silica sand and limestone. Specific examples of sand include natural silica sand. Among these, silica sand is preferred. The particle size of the silica sand is not particularly limited. For example, silica sand having a particle size of 4 or more and 7 or less as specified in JIS G 5901:2016 can be used. Appropriate silica sand can be used depending on the application method of the road paving composition. For example, when application is performed by coating with a rake, brush, etc., the particle size of the silica sand is preferably 5 or more and 6 or less. Also, when application is performed by spraying with a spray, etc., the particle size of the silica sand is preferably 6 or more and 7 or less. These aggregates can be used alone or in combination of two or more. From the viewpoint of abrasion resistance, the content of the aggregate is, per 100 parts by mass of the emulsion solids, 300 parts by mass or more, more preferably 400 parts by mass or more, even more preferably 450 parts by mass or more, and is preferably 800 parts by mass or less, even more preferably 700 parts by mass or less, more preferably 600 parts by mass or less.
[0034] [Other ingredients] In addition to the above-mentioned components, the road paving composition may further contain various known additives such as film-forming assistants, anti-stripping agents, antioxidants, process oils, and the like. The road paving composition and color paving coating composition can be given flexibility and further improved strength after application by using a film-forming assistant in combination. The film-forming assistant can be an aqueous dispersion of a thermoplastic resin having a glass transition temperature of 20° C. or less. The glass transition temperature of the thermoplastic resin is preferably −50° C. or more, more preferably −20° C. or more, and preferably 5° C. or less, more preferably 0° C. or less. Specific examples of thermoplastic resins include styrene-acrylic resins, poly(meth)acrylic acid esters, polyvinyl acetate, ethylene-vinyl acetate copolymers, polyurethane, styrene-butadiene rubber, acrylonitrile-butadiene rubber, isoprene rubber, chloroprene rubber, natural rubber, and aqueous latexes thereof. Among these, styrene-acrylic aqueous dispersions are preferred from the viewpoint of imparting flexibility. From the viewpoint of abrasion resistance, the content of the film-forming auxiliary is 1 part by mass or more, more preferably 2 parts by mass or more, and even more preferably 3 parts by mass or more, per 100 parts by mass of the emulsion solids, and is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and more preferably 100 parts by mass or less.
[0035] [Colored pavement coating composition] The road paving composition may be a colored paving coating composition further containing a pigment. The colored paving coating composition can clearly color-code sidewalks, indicate stopping zones, etc., by using a colored surface layer.
[0036] [Pigments] The pigment may be either an organic pigment or an inorganic pigment, and lake pigments and fluorescent pigments may also be used. If necessary, these may also be used in combination with extender pigments. The pigments may be used alone or in combination of two or more. Specific examples of organic pigments include azo pigments such as azo lake pigments, insoluble monoazo pigments, insoluble disazo pigments, condensed azo pigments, and chelate azo pigments; and polycyclic pigments such as phthalocyanine pigments, perylene pigments, perinone pigments, anthraquinone pigments, quinacridone pigments, dioxazine pigments, thioindigo pigments, isoindolinone pigments, isoindoline pigments, quinophthalone pigments, diketopyrrolopyrrole pigments, threne pigments, and metal complex pigments. Specific examples of inorganic pigments include carbon blacks such as furnace black, thermal lamp black, acetylene black, and channel black; metal oxides such as titanium oxide, zinc oxide, iron oxide, red iron oxide, and chromium oxide; and pearlescent pigments. Examples of the extender pigment include silica, calcium carbonate, and talc. The hue is not particularly limited, and any chromatic pigment such as yellow, magenta, cyan, blue, red, orange, green, etc. can be used. The pigment content is preferably 2% by mass or more, more preferably 4% by mass or more, even more preferably 6% by mass or more, and preferably 20% by mass or less, more preferably 16% by mass or less, even more preferably 10% by mass or less, based on 100 parts by mass of the solid content of the emulsion.
[0037] [Paving method] By applying the road paving composition or colored pavement coating composition of the present invention to a pavement surface, which is an asphalt pavement layer or a concrete pavement layer, a surface layer or a colored surface layer made of a resin can be formed. Therefore, the present invention also provides a method for paving a road, which comprises a step of applying the road paving composition or colored paving coating composition onto a paved surface. Application onto the pavement surface can be carried out, for example, by coating with a rake, brush, etc., or by spraying with a spray, etc. The road paving composition and colored paving coating composition can react and harden at room temperature due to the evaporation of water, so the application temperature can be room temperature (for example, 20°C or higher and 35°C or lower). EXAMPLES
[0038] Various physical properties were measured and evaluated by the following methods. In the following examples and comparative examples, parts and percentages are by weight unless otherwise specified.
[0039] (1) Measurement of the softening point of polyamide The softening point of the polyamide was measured by the ring and ball method specified in "JIS K2207:2006 Petroleum Asphalt."
[0040] (2) Measurement of the acid value of polyamide The acid value of the polyamide was measured based on the method of JIS K0070: 1992. However, the measurement solvent was changed from the mixed solvent of ethanol and ether specified in JIS K0070: 1992 to a mixed solvent of methanol and chloroform (methanol:chloroform = 1:1 (volume ratio)).
[0041] (3) Measurement of amine value of polyamide The amine value of polyamide was measured based on the method of JIS K7237:1995, except that the measurement solvent was changed from the mixed solvent of o-nitrotoluene and acetic acid specified in JIS K7237:1995 to a mixed solvent of methanol and chloroform (methanol:chloroform = 1:1 (volume ratio)).
[0042] (4) Measurement of heat of crystallization (ΔHc) of polyamide Using a differential scanning calorimeter "DSC Q20" (manufactured by TA Instruments Japan Co., Ltd.) conforming to JIS-K7121, 0.01 to 0.02 g of the sample was weighed into an aluminum pan, heated to 150°C at a heating rate of 20°C / min, and cooled to -10°C at a cooling rate of 5°C / min to obtain a crystallization exothermic curve. The heat quantity was calculated from the area of the exothermic peak obtained from the crystallization exothermic curve, and this was taken as the heat quantity of crystallization (ΔHc).
[0043] (5) Volume median particle size of polyamide emulsion (D 50 ) Measurement Measuring device: Laser diffraction type particle size measuring device (manufactured by Horiba Ltd.) Measurement conditions: Distilled water was added to the sample to be measured, and the concentration was adjusted so that the particle size of 30,000 particles could be measured in 20 seconds. After that, the particle sizes of 30,000 particles were measured, and the volume median particle size (D 50 ) was sought.
[0044] (6) Measurement of solids concentration of polyamide emulsion Using an infrared moisture meter (Kett Electric Laboratory, "FD-230"), 5 g of the measurement sample was dried at a drying temperature of 150°C and measurement mode 96 (monitoring time 2.5 minutes, fluctuation range 0.05%), and the moisture content (mass%) of the measurement sample was measured. The solid content was calculated according to the following formula. Solid concentration (mass%) = 100-moisture (mass%)
[0045] Production Example 1 (Production of Polyamide PA1) The carboxylic acid components including oleic acid (manufactured by Kao Corporation, product name: Lunac OV), propionic acid, and polymerized fatty acid (dimer acid, manufactured by Tsuno Food Industry Co., Ltd., product name: Tsunodim 205) and the amine components consisting of ethylenediamine (EDA), hexamethylenediamine (HMDA), and isophoronediamine (IPDA) were placed in a four-neck round-bottom flask equipped with a thermometer, a stirring system, a dehydration tube, and a nitrogen blowing tube in the amounts shown in Table 1. The mixture was stirred, and a small amount of nitrogen was blown in to prevent discoloration of the contents, and then the mixture was reacted at 210°C for 3 hours and then under reduced pressure (13.3 kPa) for 2 hours. After cooling, the mixture was pulverized to obtain polyamide PA1. The results are shown in Table 1.
[0046] Production Examples 2 to 8 (Production of Polyamides PA2 to PA8) Polyamides PA2 to PA8 were obtained in the same manner as in Production Example 1, except that the compositions of the carboxylic acid component and the amine component were as shown in Table 1. The results are shown in Table 1.
[0047] [Table 1]
[0048] Production Example 9 (Production of polyamide emulsion Em1, phase inversion emulsification) In a 2L container equipped with a stirrer "Three One Motor BL300" (manufactured by Shinto Scientific Co., Ltd.), a reflux condenser, a dropping funnel, a thermometer and a nitrogen inlet tube, 90 g of the polyamide PA1 obtained in Production Example 1, 10 g of monocarboxylic acid C1 (manufactured by Tokyo Chemical Industry Co., Ltd., Isostearic Acid: also known as 2,2,4,8,10,10-Hexamethylundecane-5-carboxylic Acid), 50 g of isopropyl alcohol (IPA) and 50 g of tetrahydrofuran (THF) were placed, and the polyamide was dissolved at 50° C. for 3 hours. After cooling to 30° C., a neutralizing agent N1 (2-dimethylaminoethanol) was added to the solution so that the degree of neutralization with respect to the acid value of polyamide PA1 and carboxylic acid compound C1 was 100 mol%, and the solution was stirred for 60 minutes. Next, while maintaining the temperature at 30°C, 400g of deionized water was added over 120 minutes while stirring at 200r / min, and phase inversion emulsification was performed. After heating to 50°C, isopropyl alcohol and THF were distilled off under reduced pressure to obtain an aqueous dispersion. After cooling the aqueous dispersion to 30°C while stirring, it was filtered through a 300 mesh wire net to obtain polyamide emulsion Em1. The results are shown in Table 2.
[0049] Production Examples 10 to 16 (Production of Polyamide Emulsions Em2 to Em8) Polyamide emulsions Em2 to Em8 were obtained in the same manner as in Production Example 9, except that the types of polyamide were as shown in Table 2. The results are shown in Table 2.
[0050] Production Examples 17 to 24 (Production of Polyamide Emulsions Em9 to Em16) Polyamide emulsions Em9 to Em16 were obtained in the same manner as in Production Example 9, except that the amount of carboxylic acid compound used or the type of carboxylic acid compound was as shown in Table 2. The results are shown in Table 2.
[0051] Production Example 25 (Production of polyamide emulsion Em17, high pressure emulsification) A sealable pressure-resistant 2-liter glass container equipped with a stirrer and a heater was charged with 90 g of the polyamide PA1 obtained in Production Example 1, 10 g of monocarboxylic acid C1 (Tokyo Chemical Industry Co., Ltd., Isostearic Acid: also known as 2,2,4,8,10,10-Hexamethylundecane-5-carboxylic Acid), 50 g of isopropyl alcohol (IPA), 50 g of tetrahydrofuran (THF), and 100 g of deionized water, and neutralizing agent N1 (2-dimethylaminoethanol) was added so that the degree of neutralization with respect to the acid values of polyamide PA1 and monocarboxylic acid C1 was 100 mol %. The system was heated while stirring at a rotation speed of 200 r / min, and heated and stirred at 120°C for 1 hour. After that, it was cooled to 30°C while stirring, and 300g of deionized water was added. The obtained aqueous dispersion was transferred to a 2L container equipped with a stirrer "Three One Motor BL300" (manufactured by Shinto Scientific Co., Ltd.), a reflux condenser, a dropping funnel, a thermometer, and a nitrogen inlet tube, and heated to 50°C. After that, isopropyl alcohol and THF were distilled off under reduced pressure to obtain an aqueous dispersion. The aqueous dispersion was cooled to 30°C while stirring, and then filtered through a 300 mesh wire net to obtain a polyamide emulsion (Em17). The results are shown in Table 2. is shown in Table 2.
[0052] [Table 2]
[0053] Example 1 <Paint preparation> In a 1 L stainless steel beaker, 100 g of an aqueous dispersion of polyamide emulsion Em1 obtained in Production Example 9, adjusted to a solid content of 20% by adding deionized water, 4.3 g of acrylic emulsion (PEGAL 809, manufactured by Koatsu Gas Kogyo Co., Ltd.) as a film-forming aid, 133 g of Toyoura silica sand (manufactured by Toyoura Silica Mining Co., Ltd.), and hardener B1 (epoxy-based silane coupling agent, manufactured by Shin-Etsu Chemical Co., Ltd.: KBM-402) were placed and mixed for 10 minutes at 200 rpm using a mixer equipped with a turbine-type mixing blade to obtain a paint composition for road paving. <Coating film preparation> The obtained paint was applied to a slate board (test piece sold by AS ONE Co., Ltd.; slate board) in an amount of 10.5 g (1.0 kg / 1.0 m) 2 ) was applied and smoothed with a rubber spatula. It was then left to dry at room temperature for 2 hours. The process of applying 10.5 g of paint and drying was repeated three times in total, resulting in three layers. After that, the coating was left to dry at room temperature for three days to prepare a coating film sample.
[0054] <Wear resistance test> The prepared coating sample was fixed to an abrasion resistance tester (AB-201 Sutherland type ink lab tester, manufactured by Tester Sangyo Co., Ltd.), and a weight of 3090 g was placed on the top of the base on which sandpaper (#40 cloth sandpaper, manufactured by Trusco Nakayama Co., Ltd.) was fixed to the friction surface, and a load of 7.8 kN / m was applied to the sample. 2 The tester was operated and the sandpaper was replaced with a new one and the abrasion debris removed from the sample every 1000 times, for a total of 3000 abrasions. The weight loss before and after abrasion was measured and recorded as abrasion resistance. The results are shown in Table 3.
[0055] <Pot life evaluation> 10 g of the prepared paint was placed in a 105 ml polyethylene container (Sampler Container, manufactured by Sanplatec Co., Ltd.) and left to stand at room temperature for 1 hour. After standing, the container was gently turned sideways to allow the paint to flow. If the paint reached the top of the container opening within 20 seconds, it was deemed to have passed the test, and the container was left to stand for another hour at room temperature. The time when the paint no longer reached the top of the container opening within 20 seconds was regarded as the pot life. The results are shown in Table 3.
[0056] Examples 2 to 8 Except for the type of curing agent or the amount of curing agent used being as shown in Table 3, coating materials were prepared, coating film samples were prepared, and abrasion resistance tests were carried out in the same manner as in Example 1. The results are shown in Table 3.
[0057] Examples 9 to 24 Except for using the polyamide emulsions shown in Table 3, coating compositions were prepared, coating film samples were prepared, and abrasion resistance tests were carried out in the same manner as in Example 1. The results are shown in Table 3.
[0058] Comparative Example 1 Except for not using a curing agent, a coating material was prepared and a coating film sample was prepared and subjected to an abrasion resistance test in the same manner as in Example 1. The results are shown in Table 3.
[0059] [Table 3]
[0060] From Table 3, it can be seen that the road composition of the present invention, which combines a polyamide emulsion with a specific curing agent, has excellent abrasion resistance. Furthermore, when a polyamide is used in combination with a curing agent, a decrease in pot life can be a problem. The road paving composition of the present invention has a good pot life, even though a curing agent is used in combination.
Claims
1. Contains a polyamide emulsion (A) and an epoxy silane coupling agent (B), the polyamide emulsion (A) contains a polyamide (a1) and at least one carboxylic acid compound (a2) selected from a branched-chain aliphatic carboxylic acid having from 8 to 24 carbon atoms and a secondary carboxy group-containing linear aliphatic carboxylic acid having from 8 to 24 carbon atoms; The acid value of the polyamide (a1) is 15 mgKOH / g or more and 50 mgKOH / g or less. Road paving composition.
2. 2. The road paving composition according to claim 1, wherein the epoxy silane coupling agent (B) is an epoxy silane coupling agent having a dialkoxysilyl group.
3. 3. The road paving composition according to claim 2, wherein the dialkoxysilyl group is a dimethoxysilyl group.
4. The road paving composition according to any one of claims 1 to 3, wherein the content of the epoxy silane coupling agent (B) is 5 parts by mass or more and 12 parts by mass or less per 100 parts by mass of the solid content of the polyamide emulsion (A).
5. The road paving composition according to any one of claims 1 to 4, wherein the mass ratio of the polyamide (a1) to the carboxylic acid compound (a2) [(a1):(a2)] is 80:20 or more and 99:1 or less.
6. The road paving composition according to any one of claims 1 to 5, wherein the heat of crystallization (ΔHc) of the polyamide (a1) is 2 J / g or more and 13 J / g or less.
7. A coating composition comprising a polyamide emulsion (A) and an epoxy silane coupling agent (B), The polyamide emulsion (A) contains a polyamide (a1), The heat of crystallization (ΔHc) of the polyamide (a1) is 2 J / g or more and 13 J / g or less, The acid value of the polyamide (a1) is 15 mgKOH / g or more and 50 mgKOH / g or less. Road paving composition.
8. A road paving composition as described in claim 7, wherein the epoxy silane-based coupling agent (B) is an epoxy silane-based coupling agent having a dialkoxysilyl group.
9. A road paving composition as described in claim 7 or 8, wherein the polyamide emulsion (A) further contains at least one carboxylic acid compound (a2) selected from branched-chain aliphatic carboxylic acids having 8 to 24 carbon atoms and linear aliphatic carboxylic acids containing a secondary carboxy group having 8 to 24 carbon atoms.
10. A road paving composition as described in claim 9, wherein the mass ratio of polyamide (a1) to carboxylic acid compound (a2) [(a1):(a2)] is 80:20 or more and 99:1 or less.
11. The road paving composition according to any one of claims 1 to 10, further comprising silica sand.
12. 12. The road paving coating composition according to claim 11, further comprising a pigment.
13. A method for paving a road, comprising the steps of mixing a polyamide emulsion (A) and an epoxy silane coupling agent (B) and applying the resulting mixture to a pavement surface, in the step of mixing the polyamide emulsion (A) and the epoxy silane coupling agent (B), the polyamide emulsion (A) contains a polyamide (a1) and at least one carboxylic acid compound (a2) selected from a branched-chain aliphatic carboxylic acid having from 8 to 24 carbon atoms and a secondary carboxy group-containing linear aliphatic carboxylic acid having from 8 to 24 carbon atoms, A road paving method, wherein the acid value of the polyamide (a1) is 15 mgKOH / g or more and 50 mgKOH / g or less.
14. A method for paving a road, comprising the steps of mixing a polyamide emulsion (A) and an epoxy silane coupling agent (B) and applying the resulting mixture to a pavement surface, In the step of mixing the polyamide emulsion (A) and the epoxy silane-based coupling agent (B), the polyamide emulsion (A) contains a polyamide (a1), The heat of crystallization (ΔHc) of the polyamide (a1) is 2 J / g or more and 13 J / g or less, A road paving method, wherein the acid value of the polyamide (a1) is 15 mgKOH / g or more and 50 mgKOH / g or less.
Citation Information
Patent Citations
Low viscosity aqueous emulsion of polyamide resin and preparation thereof
JP2000007787A
Binder composition for road construction
JP2004124040A
Road paving composition and paving body making use thereof
JP2005126998A
Aqueous polyamide resin dispersion, method for producing the same, and laminate
JP2011094072A
Aqueous dispersion and method for producing the same
JP2012031261A